Effect of medium solvent ratios on morphologies and optical properties of α-ZnMoO4, β-ZnMoO4 and ZnMoO 4·0.8H2O crystals synthesized by microwave-hydrothermal/solvothermal method - Keereeta Y. (Academic Press, 2014)
ZnMoO4 with different morphologies were successfully synthesized by microwave hydrothermal and microwave solvothermal methods, without the use of any additives. The different crystalline phases (α-ZnMoO4, β-ZnMoO4 and ZnMoO4·0.8H2O), morphologies and optical properties of the samples were studied by X-ray diffraction, electron microscopy and spectroscopy, and were found to be influenced by the length of reaction time and the different volume ratios of ethylene glycol (EG) to water as medium solvents. In this research, the direct energy gap (Eg) and photonic emission wavelength were evaluated to be 3.13-3.51 eV and 366 nm, respectively. © 2014 Published by Elsevier Ltd.